East-West Dialogue - Chen, Lujun; Pohl, Karl-Heinz.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This Open access book is a collection of interviews published by China News Service, a Beijing-based news agency, in its West-East Talk column. It has been divided into five sections: Mutual Learning Among Civilizations, Hot Issues, About China, Sino-U.S. Relations and Cultural Collision. The interviews are with more than 50 eminent scholars, scientists, politicians, authors, etc., from different parts of the world as well as China, who have an association with China and see the real China beyond the stereotypes. Besides current global issues, the book also covers Chinese culture, history as well as China-U.S. relations, described as one of the most important bilateral relationships in the world today. The book aims to build a platform for dialogue among different civilizations and appreciate the harmony within diversity of different cultures, especially of the East and West. We hope it will foster tolerance and rationality, dispelling the misconceptions about China in particular. Chen Lujun, born in January 1970, is a senior editor. Since November 2019, he has been the president of China News Service. He has won China News Awards several times and entered the list of China s cultural celebrities i.e. Four Batches of Top Experts released by the Publicity Department. Karl-Heinz Pohl, a well-known German sinologist and professor at Trier University, was born in Saarlouis, Germany in 1945. He was professor of Chinese Literature and History of Ideas at Tübingen University and had the chair of Chinese Studies at Trier University.
Preface -- I. Mutual Learning Among Civilizations -- II. Hot Issues -- III. About China -- IV. Sino-U.S. Relations -- V. Cultural Collision.
Keywords: Ethnology; Culture; China -- History; United States -- History; Globalization; International relations; Regional Cultural Studies; History of China; US History; Globalization; International Relations